Molecular structure engineering of dielectric fluorinated polymers for enhanced performances of triboelectric nanogenerators. (November 2018) - Kim, Minsoo P.; Lee, Youngoh; Hur, Yoon Hyung; Park, Jonghwa; Kim, Jinyoung; Lee, Youngsu; Ahn, Chang Won; Song, Seung Won; Jung, Yeon Sik; Ko, Hyunhyub
Abstract: Fluorinated polymers have been widely used in triboelectric sensors, displays, and energy harvesting devices because of their superior electron affinity, which leads to the negative triboelectric materials. While previous reports have shown that the control of dielectric constants of fluorinated polymers can increase the triboelectric output performance, the exact relationship between the molecular structures of fluorinated polymers and the resulting triboelectric properties is still elusive. In this study, we demonstrate that the molecular chain structures of the fluorinated polymers depending on the number of fluorine units, the molecular weight ( M w ), and conditions such as spin rate and annealing temperature directly affect the relative dielectric constants of dielectric layers and the triboelectric polarity, which are closely related to the triboelectric output performance. We observe that the polymer chain packing structures result in the increase of the relative dielectric constants, thus leading to the improvement of triboelectric output currents. Among the fluorinated polymers used in this study, a poly (2, 2, 2-trifluoroethyl methacrylate) polymer with three fluorine units and M w of ~ 20 kg/mol shows the best triboelectric output performance. Our molecular engineering strategy to control the dielectric constants of fluorinated polymers can be a robust platform for the fundamental studies of triboelectric materials and their applications in diverse energy harvesting and sensing devices. Graphical abstract: We present the molecular structure engineering of fluorinated dielectric polymer for enhancement of triboelectric performance, which depends on different number of fluorine units, molecular weight, and process condition. The molecular packing structure affects the change of surface potential as well as the free volume in the polymer matrix, resulting in the control of dielectric constant and final triboelectric performances. Our molecular engineering strategy can be a feasible method to modify the triboelectric output performance and can be extended into diverse energy harvesting and sensing devices. fx1 Highlights: Synthesized fluorinated polymer with different fluorine chain for the triboelectric properties. Demonstrated correlation between polymer chain structures and relative dielectric constants. Tuning the dielectric constants can control the triboelectric output performances.